Oligo(aryl-triazole)s CH⋯Cl− interactions guide chloride efficient and selective transmembrane transport. Issue 89 (20th October 2016) - Chen, Sujun; Zhang, Sitong; Bao, Chunyan; Wang, Chenxi; Lin, Qiuning; Zhu, Linyong
Abstract : Using specific C–H⋯Cl − interactions, oligo(aryl-triazole) based transporters realized efficient/selective Cl − transmembrane transport by adjusting their molecular lipophilicity and anion affinity. Abstract : A series of oligo(aryl-triazole)s (compounds1–8 ) have been synthesized and served as transmembrane anion transporters by only CH⋯Cl − interactions. This work confirms their role in the activity of anion transport. By changing the lipophilicity and anion affinity of the compounds, efficient anion transport with remarkable Cl − vs. HCO3 − selectivity was achieved.